2002
DOI: 10.1053/eujp.2001.0307
|View full text |Cite
|
Sign up to set email alerts
|

Morphine responsiveness in a group of well‐defined multiple sclerosis patients: A study with i.v. morphine

Abstract: Pain in multiple sclerosis (MS) is more common than has previously been believed. About 28% of all MS patients suffer from central pain (CP), a pain that is difficult to treat. In the present study we have investigated the responsiveness of this pain to morphine. Fourteen opioid-free patients (eight woman and six men) with constant, non-fluctuating, long-lasting CP caused by MS were investigated. Placebo (normal saline), morphine and naloxone were given intravenously in a standardized manner. The study design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 46 publications
(63 reference statements)
2
33
0
2
Order By: Relevance
“…If opioids are used in treatment escalation for central pain, high dosages are required in most cases [75] and will therefore not be tolerated by many on long-term treatment, e.g. morphine 9–30 mg/day (class II evidence [76]).…”
Section: Ms-related Pain Syndromesmentioning
confidence: 99%
“…If opioids are used in treatment escalation for central pain, high dosages are required in most cases [75] and will therefore not be tolerated by many on long-term treatment, e.g. morphine 9–30 mg/day (class II evidence [76]).…”
Section: Ms-related Pain Syndromesmentioning
confidence: 99%
“…Despite the widespread use of opioids for chronic pain, remarkably few studies have investigated their efficacy for the neuropathic pain of MS. A single dose using intravenous morphine decreased MS pain (>50% pain reduction) in 29% of the 14 patients involved in a single-blind non-randomized placebo-controlled trial (Kalman et al, 2002). Opioid receptors appear to mediate the analgesic effect of morphine, as it was reversed by naloxone.…”
Section: Clinical Pharmacology Of Pain In Msmentioning
confidence: 99%
“…In MS patients the efficacy of opioids in CP has not been documented. In a nonrandomized, placebo-controlled study [48] it was found that IV morphine only had an analgesic effect in a minority (4/14) of the MS patients with central pain.…”
Section: Pharmacologic Intervention In Ms Associated Cp (Box 213)mentioning
confidence: 99%
“…The same is true of opioids and tramadol, in which long-term side effects and drug addiction are concerns. Small studies in CP have failed to document an effect of opioids in stroke patients [16] and MS patients [48]. However, opioids as well as tramadol are effective in reducing peripheral neuropathic pain and may also be considered in refractory CP.…”
Section: Treatment Algorithm In Cpmentioning
confidence: 99%